Comparing guideline-based care quality for inflammatory bowel disease and rheumatoid arthritis patients within a medical home. (2nd June 2016) - Caldera, Freddy; Saha, Sumona; Wald, Arnold; Cooley, David M.; Zhao, Ying-Qi; Li, Zhanhai; Bartels, Christie M.
ABSTRACT: Background : Rheumatoid arthritis (RA) and inflammatory bowel disease (IBD) patient populations face similar risks of chronic immunosuppression including corticosteroid use. We compared the receipt of preventive services between IBD and RA populations according to published quality metrics. Methods : We defined a single-center cohort of patients with IBD or RA receiving specialty and primary care. Electronic health record abstraction assessed quality metrics, sociodemographics, comorbidity, and utilization. Comparisons used multivariate odds ratios and Student's t-tests. Results : 218 RA and 190 IBD patients were included. In multivariate analysis, IBD patients were less likely to receive pneumococcal vaccination (OR=0.29, 95% CI: 0.11-0.85), while RA patients underwent glucocorticoid-induced osteoporosis screening more often (100% vs. 82.5%, p = 0.023). Conclusions : Gastroenterologists can improve care quality for IBD patients by assuming greater responsibility for preventive care in IBD patients and/or collaborating with primary care and health systems to improve preventive care delivery.